Scenes of indigenous, afro-brazilian, african and timorian cultural lives in contemporary times - Salome (Org.), Nyambura; Paulino (Org.), Itamar Rodrigues; Júnior (Org.), Augusto da Silva (NJINGA e SEPÉ: Revista Internacional de Culturas, Línguas Africanas e Brasileiras (ISSN: 2764-1244), 2023)
This special issue brings together articles that present to society elements that compose scenes of indigenous, Afro-Brazilian, African and Timorese cultural lives in contemporary times. The issue is made up of joint texts that bring together a range of themes that allow for a frankly transdisciplinary dialogue on the contemporaneity of peoples of indigenous, Afro-Brazilian, African and Timorese roots. It points to diverse and revealing scenarios in which these peoples deal with most challenges and advances in social, economic, cultural, environmental and educational development. This issue has brought together 24 articles with approaches, trends and methodologies, in addition to historical, epistemological, aesthetic and hermeneutical points, and diverse contexts to discuss the most varied sets of elements that make up the space in Brazil, Africa and East Timor where human beings live, with their identity and memory. The texts articulate academic themes such as literature, philosophy, culture, linguistics, sociology, law; and present practical scenarios that update topics such as human development processes, teacher training, decolonization processes, sexual violence against children, studies of black festive organizations in the Amazon region, basic sanitation in African countries, among others, placing them on the global agenda of contemporary research processes and paths. The articles and poems also articulate contexts and narratives, institutional arrangements and state capacities, practices and strategies associated with the development of human societies and the redefinitions of their behaviour in relation to the environment, food security, climate change, democracy, citizenship, exposing urgent issues such as prejudice, discrimination and intolerance in the face of sociocultural differences; in addition to promoting rethinking about the relationship between diversity and inequality that persist in existing among peoples.